2016
DOI: 10.1186/s12263-016-0528-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genome-wide gene expression response in peripheral blood mononuclear cells between young and old men upon caloric restriction

Abstract: BackgroundCaloric restriction (CR) is considered to increase lifespan and to prevent various age-related diseases in different nonhuman organisms. Only a limited number of CR studies have been performed on humans, and results put CR as a beneficial tool to decrease risk factors in several age-related diseases. The question remains at what age CR should be implemented to be most effective with respect to healthy aging. The aim of our study was to elucidate the role of age in the transcriptional response to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The effect was significant only among the elderly mice. This was not surprising since, upon external stimuli, an age-dependent differential gene expression response is commonly observed in both animal and human studies (60)(61)(62). Furthermore, differential age-related mRNAs expression was also observed despite the similar micronuclei frequency observed in both age groups treated with CP and 600 mg/kg PE-E.…”
Section: Regulation Of Main Signaling Pathways By Pleurotus Eryngii E...mentioning
confidence: 56%
“…The effect was significant only among the elderly mice. This was not surprising since, upon external stimuli, an age-dependent differential gene expression response is commonly observed in both animal and human studies (60)(61)(62). Furthermore, differential age-related mRNAs expression was also observed despite the similar micronuclei frequency observed in both age groups treated with CP and 600 mg/kg PE-E.…”
Section: Regulation Of Main Signaling Pathways By Pleurotus Eryngii E...mentioning
confidence: 56%
“… 16 , 17 , 18 , 19 , 20 Expression profiles and corresponding survival information from two LIHC validation cohorts were obtained from the project ‘LIRI-JP’ of the International Cancer Genome Consortium (ICGC) and GSE14520. 21 Expression profiles and corresponding grouping information from the DR-related clinical trial and the obesity-related cohort were obtained from GSE63117 and GSE69039, 22 , 23 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They found that genotypes and coffee consumption affect risk of RA and effectiveness of methotrexate treatment [118]. Based on genome-wide gene expression response data, Van Bussel et al [185] have theorised that a brief term caloric restriction is effective in downregulating gene sets involved in the immune response in young men. Moreover, a recent multi-omics study has found that caloric restriction ameliorates insulin sensitivity in humans [186], while studies in human obesity and insulin resistance have shown a clear relationship between decreased insulin sensitivity, the chronic activation of pro-inflammatory signaling pathways and RA activity.…”
Section: Nutrigenomics Approach To Rheumatoid Arthritismentioning
confidence: 99%